2013
DOI: 10.3390/bios3040419
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Fluorescence Resonance Energy Transfer (FRET)-Based DNA Biosensor for Detection of Synthetic Oligonucleotide of Ganoderma boninense

Abstract: An optical DNA biosensor based on fluorescence resonance energy transfer (FRET) utilizing synthesized quantum dot (QD) has been developed for the detection of specific-sequence of DNA for Ganoderma boninense, an oil palm pathogen. Modified QD that contained carboxylic groups was conjugated with a single-stranded DNA probe (ssDNA) via amide-linkage. Hybridization of the target DNA with conjugated QD-ssDNA and reporter probe labeled with Cy5 allows for the detection of related synthetic DNA sequence of Ganoderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 10 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…[163] Applying synthesized biocompatible nanosized CdSe quantum dots (QDs) with the DNA probe, Bakhori et al exploited the fluorescence resonance energy transfer (FRET) technology to detect the synthetic oligonucleotide of DNA for Ganoderma boninense, an oil palm pathogen. [164] The FRET approach with QDs could determine the hybridization process, demonstrating a high sensitivity and a low detection limit of 3.55 × 10 -9 m. Due to a high surface-to-volume ratio, gold nanoparticles (Au-NPs) have been employed for pathogen detection with low detection limits and high specificity. As shown in Figure 6f, Zhao et al reported a dual amplified electrochemical sandwich enzyme-linked immunoassay (ELISA) to tag the Au-NPs with the Horseradish peroxidase (HRP) antibodies to detect Pantoea stewartii sbusp.…”
Section: Soil Insect/pest Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[163] Applying synthesized biocompatible nanosized CdSe quantum dots (QDs) with the DNA probe, Bakhori et al exploited the fluorescence resonance energy transfer (FRET) technology to detect the synthetic oligonucleotide of DNA for Ganoderma boninense, an oil palm pathogen. [164] The FRET approach with QDs could determine the hybridization process, demonstrating a high sensitivity and a low detection limit of 3.55 × 10 -9 m. Due to a high surface-to-volume ratio, gold nanoparticles (Au-NPs) have been employed for pathogen detection with low detection limits and high specificity. As shown in Figure 6f, Zhao et al reported a dual amplified electrochemical sandwich enzyme-linked immunoassay (ELISA) to tag the Au-NPs with the Horseradish peroxidase (HRP) antibodies to detect Pantoea stewartii sbusp.…”
Section: Soil Insect/pest Sensorsmentioning
confidence: 99%
“…exploited the fluorescence resonance energy transfer (FRET) technology to detect the synthetic oligonucleotide of DNA for Ganoderma boninense , an oil palm pathogen. [ 164 ] The FRET approach with QDs could determine the hybridization process, demonstrating a high sensitivity and a low detection limit of 3.55 × 10 –9 m . Due to a high surface‐to‐volume ratio, gold nanoparticles (Au‐NPs) have been employed for pathogen detection with low detection limits and high specificity.…”
Section: Advances Of Typical Soil Sensorsmentioning
confidence: 99%
“…The quantum dots unit utilizes Förster Resonance Energy Transfer (FRET) modeling in its detection operation [ 27 ]. By using a similar technology, Bakhori et al [ 28 ] detected synthetic oligonucleotide of Ganoderma boninense. However, this work employed adjusted quantum dots with carboxylic groups that are then conjugated using a DNA probe.…”
Section: Related Literaturementioning
confidence: 99%
“…However, this work employed adjusted quantum dots with carboxylic groups that are then conjugated using a DNA probe. This gave rise to an improved sensitivity of the system, yielding 3.55 × 10 −9 M as the detection limit [ 28 ].…”
Section: Related Literaturementioning
confidence: 99%
“…By exploiting the photoluminescence of GO and quenching ability of gold nanoparticles (AuNPs) for organic fluorophores, a series of FRET-based biosensors of GO arrays were realized towards aptasensing [ 105 ] and immunosensing [ 106 ] of proteins, and for the detection of sequence-specific DNA hybridization [ 107 , 114 ]. Correspondingly, probe biomolecules including aptamers [ 105 ], antibodies [ 106 ], ssDNAs and molecular beacons (MBs) [ 115 , 116 ] have been utilized in these selective FRET assays of proteins and nucleic acids (e.g., DNA bases and sequences).…”
Section: Graphenementioning
confidence: 99%